2010
DOI: 10.4038/jfa.v1i2.1799
|View full text |Cite
|
Sign up to set email alerts
|

ICT Adoption and Its’ Implications for Agriculture in Sri Lanka

Abstract: Agriculture is the backbone of the Sri Lankan economy and it constantly experiences with advances in technology. Because of the rapid development of Information and Communication Technology (ICT) in the world, each organization or person has to concern their products and services more towards modernized and ICT related manner. This research contribute to understand the adoption & use of ICT, identify the constraints associated with ICT use and propose recommendations with managerial implications towards the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…This proves the potential of ICT to reduce the cost of production of small-growers in Sri Lanka. Jayathilake et al (2008) reported that the use of ICT applications in the corporate tea sector in Sri Lanka was comparatively high and mobile communication was common among all plantations managers.…”
Section: Ict Use In Sri Lankamentioning
confidence: 99%
See 1 more Smart Citation
“…This proves the potential of ICT to reduce the cost of production of small-growers in Sri Lanka. Jayathilake et al (2008) reported that the use of ICT applications in the corporate tea sector in Sri Lanka was comparatively high and mobile communication was common among all plantations managers.…”
Section: Ict Use In Sri Lankamentioning
confidence: 99%
“…Moreover, the factors such as lack of ICT proficiency, lack of ICT benefit awareness, too hard to use, lack of technological infrastructure, cost of technology, trust level in the ICT system, lack of training, system integration and software availability could also limit the use of ICT by horticultural farmers in Belgium (Taragola and Lierde, 2005). Warren et al (2000) reported that, the adoption of ICT is positively associated with the farm size, education level of the farmer and negatively associated with the age of the farmers.Tea producers and poultry farmers in Kurunagala district have stressed that the cost of technology, lack of training, trust level on the ICT system, lack of ICT proficiency and lack of technological infrastructure are thresholds for ICT adoption and use (Jayathilake et al,2008). A study conducted by Aker (2010) recommended that the training of the extension workers should include computer literacy to enable them access to internet and other electronic information technologies.…”
Section: Ict Use In Agricultural Extensionmentioning
confidence: 99%
“…In the area of infrastructure, Jayathilake, Jayaweera and Waidyasekera (2008) identified lack of technological infrastructure as one threshold for ICT adoption and use in Sri Lanka agriculture. Also, Bwalya (2009) found that lack of adequate ICT infrastructure contributes much to the delay in appropriate e-government adoption and utilisation in Zambia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since, information acts as a key player, farmer awareness, availability, accessibility and usability of different ICT appliances may decide the overall productivity in the agriculture sector. At present, there have been many ICT tools which introduced to farmers, traders and other actors within the agricultural value chain by both private and public entities in Sri Lanka [10]. Those tools provide information related to production and marketing.…”
Section: Introductionmentioning
confidence: 99%